REFLECTION OF THE COVID-19 PANDEMIC ON THE SYPHILIS INDEX - Eduarda Almeida de Souza, Cicera; Gouvea do Carmo e Silva, Iago; Vaz da Silva Borges, Leandro; da Costa Araújo, Paulo; Maêdya Fernandes Cruz, Francisca; Costa Silva, Karoline; Melo de Souza, Milena; Rodrigues de Sousa, Larissa; Wágner Holanda Lima, Mariel; Costa Duarte, Tamires; Souza Campos, Monique (Health and Society, 2023)
Introduction: With the arrival of the Covid-19 pandemic in Brazil and the high mortality rates, health service authorities ended up neglecting cases of syphilis, leaving this problem in the background as if the disease were not of such importance to this period. In this sense, the lack of screening, diagnosis and the lack of compulsory notification, left the population more exposed and vulnerable both to the progression of the disease and to the increase in the transmission of syphilis. Objective: To compare the incidence of cases of acquired syphilis and maternal syphilis before and during the Covid-19 pandemic, as well as to highlight the reflection of the coronavirus in the notification and clinical management of the disease. Methodology: This study was carried out through a cross-sectional analysis, whose purpose was the collection and interpretation of data that cover the epidemiological data of reported cases of syphilis before and during Covid-19. Data collection took place between July and December 2022 using the Notifiable Diseases Information System - SINAN and the Unified Health System Database - DATASUS, where the collected data are concentrated between 2018 and 2021 referring to the states of Brazil. Results and Discussion: It is important to highlight that in cases of maternal syphilis, there was a decline in notification in the year 2021, specifically in the second half. These outcomes show a correlation with Table 1, where it is noted that the confirmation of cases of acquired syphilis also had a decline in the same period of 2021. On the other hand, the literature is complemented with the findings in the databases of the System of Grievance Information. Thus, it is noted that the screening, diagnosis and treatment of syphilis is still very complex and involves other factors that relate to the public power. Conclusion: It was possible to highlight the main factors that influence the clinical diagnosis, being the isolation measures, the high rates of infection as well as the low personal demand for medical services where the moment to prioritize the level of attention is mainly focused on the symptom and suppression of the spread of the coronavirus.